Fluorescent Properties of Cancerous Liver Tissue - Van, Nguyen Thi Khanh; Hoang, Nguyen Dinh; Binh, Nguyen Thanh; Thanh, Nguyen Cong; Binh, Pham Kim (Communications in Physics, 2014)
Fluorescence spectroscopy is a technology used fruitfully for biomedical diagnostics as well as for therapeutic purposes. The fluorescent analysis method are applied in biomedical diagnostics bases on fluorescence of endogenous or exogenous fluorophores. We initially applied fluorescence spectroscopy for the study of human liver cancer (hepatocellular carcinoma) with an exogenous fluorophores, Radachlorin\(^\) 0.35%. The main aim of this study is to determine the spectral variation between normal and malignant liver tissues in 2 cases: the samples expose and non-expose to Radachlorin. The excitation wavelength used for the fluorescence measurements is 405 nm.